2004
DOI: 10.1111/j.1742-4658.2004.04506.x
|View full text |Cite
|
Sign up to set email alerts
|

Probing the mechanism of the bifunctional enzyme ketol‐acid reductoisomerase by site‐directed mutagenesis of the active site

Abstract: Ketol‐acid reductoisomerase (EC 1.1.1.86) is involved in the biosynthesis of the branched‐chain amino acids. It is a bifunctional enzyme that catalyzes two quite different reactions at a common active site; an isomerization consisting of an alkyl migration, followed by an NADPH‐dependent reduction of a 2‐ketoacid. The 2‐ketoacid formed by the alkyl migration is not released. Using the pure recombinant Escherichia coli enzyme, we show that the isomerization reaction has a highly unfavourable equilibrium constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
79
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 23 publications
4
79
0
3
Order By: Relevance
“…Recent mechanistic and crystallographic investigations of KARI have revealed that two Mg 2+ ions are required at the active site. [18] The mechanism of the rearrangement catalyzed by KARI is generally accepted as being a concerted a-ketol reaction as there is no possibility of a retro-aldol/aldol sequence. An Mg 2+ ion is required for this isomerization step.…”
mentioning
confidence: 99%
“…Recent mechanistic and crystallographic investigations of KARI have revealed that two Mg 2+ ions are required at the active site. [18] The mechanism of the rearrangement catalyzed by KARI is generally accepted as being a concerted a-ketol reaction as there is no possibility of a retro-aldol/aldol sequence. An Mg 2+ ion is required for this isomerization step.…”
mentioning
confidence: 99%
“…As there is only one KPR that has been characterized from a hyperthermophile (17), it is difficult to judge, from a biochemical viewpoint, whether the catalytic efficiency of Tm-KPR/KARI is sufficient to conclude that it can act as (27). As T. maritima lacks the classical KPR gene, the relatively higher ratio of KPR activity against KARI activity in Tm-KPR/KARI than that in the E. coli KARI may reflect the fact that the protein does function as a KPR.…”
Section: Discussionmentioning
confidence: 99%
“…Unseres Wissens wurden lediglich zwei Enzyme beschrieben, die Semipinakol-Umlagerungen (Acyloin-Umlagerungen) katalysieren: [12][13][14][15][16][17] Acetohydroxysäure-Isomeroreduktase und 1-Desoxy-d-xylulose-5-phosphat-Reduktoisomerase sind an der Valin/Isoleucin-Biosynthese [12][13][14] bzw. dem 2-C-Methyl-d-erythritol-4-phosphat(MEP)-Biosyntheseweg beteiligt (Schema 2 B bzw.…”
Section: Abbildung 2 Lc-ms-analyse Der Umsetzung Von Aurachin C (1) unclassified
“…Tyagi et al vermuten hierzu, dass die Reduktion für die sofortige Umsetzung und damit Stabilisierung des nicht begünstigten Intermediats notwendig ist. [13] …”
Section: Abbildung 2 Lc-ms-analyse Der Umsetzung Von Aurachin C (1) unclassified
See 1 more Smart Citation